Lipidomic Analysis of the Effect of Irradiation on the Flavor of Chilled Pigeon Meat - LIU Qiaoyu, CHEN Junwen, HUANG Xiaoxia, YOU Yun, CHEN Weibo, ZENG Xiaofang, CHEN Haiguang (Shipin Kexue, 2023)
In order to explore the characteristic flavor compounds and to infer the possible main flavor precursors in irradiated pigeon meat, the changes of volatile compounds and lipid metabolites in irradiated pigeon meat were analyzed by headspace solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) and ultra-high performance liquid chromatography-tandem quadrupole time-of-flight high-resolution tandem mass spectrometry (UPLC-Triple-TOF MS/MS). The results showed that hydrocarbon and aldehydes were the major volatile components in pigeon meat. There were 10 key flavor components identified, among which, nonanal, (E)-2-hexenal, decanal, hexanal, (E)-2-octenal, (E,E)-2,4-nonadienal, octanal, 2,4-decadienal, and 1-octen-3-ol substances were derived from lipid oxidation, and nonanal aldehydes such as aldehydes, decanal, and hexanal may be generated by the decomposition of oleic and linoleic acids. Fatty acids (FA), AcylCarnitine, plasmenylPE, GlcCer_NDS, AcyGlcADG, lysoPC, Cer_BS, and lysoPS were identified as significantly differential lipid subclasses. Among the 30 lipid molecules with variable importance in the projection (VIP) scores higher than two, 6 contained oleic acid (C18:1) and 10 contained linoleic acid (C18:2). Oleic acid and linoleic acid, precursors for the formation of the characteristic flavor substances of pigeon meat, may be generated by the degradation of these 16 lipid molecules.